Rethinking geoeconomics: Trade policy scenarios for Europe's economy - Andreas Baur; Florian Dorn; Lisandra Flach; Clemens Fuest (CESifo GmbH, 2023)
Recent events and rising geopolitical tensions have raised concerns about the external dependence and vulnerability of Europe's economy. Decision-makers need to rethink the playing field of geoeconomics and should be prepared for different trade policy scenarios that may arise from new geopolitical risks. We describe the EU's recent decline in importance as an international trading partner, while for the EU itself global trade dependency has increased. We show that this dependence is highly heterogeneous across different sectors and individual member states. Based on a state-of-the-art trade model we simulate the economic impact of several policy-driven de-globalization scenarios for Europe, for individual EU member states, different economic sectors, as well as for other economies around the world. Our simulations provide information about winners and losers across countries and industries. Europe's welfare losses would be largest if the EU follows a reshoring strategy and decouples from global trade. A world of geoeconomic fragmentation and trade blocs between the East and West would also cause large permanent welfare losses for Europe. Our report provides several policy recommendations for the EU's trade policy in an age of increasing geoeconomic challenges.
Keywords: 330